BaTiO3 obtained through metallic stearate precursors - Torres, C.; Crespi, Marisa Spirandeli [UNESP]; Ribeiro, Clovis Augusto [UNESP]; Zorel, H. E. (Elsevier B.V., 2003)
Metallic stearates were used as precursors to obtain BaTiO3. Barium and titanium stearate mixtures were homogenized in ball mill containing some amount of ammonium stearate. The mixture of the precursors was evaluated by simultaneous TG/ DTA and TMA, and residues from thermal decomposition were characterized by XRD and SEM. It could be verified that the residues from the thermal decomposition in both oxidant and inert atmospheres were the BaTiO3 but with characteristic morphological and crystalline aspects depending on the experimental conditions in which the mixtures of precursors were obtained. (C) 2002 Elsevier B.V. B.V. All rights reserved.
Keywords: metallic stearates; precursor powder; thermal decomposition; BaTiO3; morphology